Pengembangan Ape Box Magic Alphabet untuk Mengenalkan Huruf pada Anak Usia Dini di RA Darussalam - Hanis Adira Lubis; Sartika Dewi Harahap; Syamsiah Depalina Siregar (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The aim of the research is to develop the Box Magic Alphabet Educational Game Tool, understand the characteristics, test practicality, ensure effectiveness and describe the difficulties experienced by students and educators in using the Box Magic Alphabet Educational Game Tool. The method used is Research and Development research using the ADDIE development model. The results of this research are: (1) The Box Magic Alphabet Educational Game Tool Development Process was developed using the ADDIE model. Based on the results of the Box Magic Alphabet product assessment instrument, it is said to be very good as a learning medium for students to recognize letters. The Box Magic Alphabet product that was developed also produced a guidebook created to make it easier for teachers in the process of making and using the Box Magic Alphabet. (2) Characteristics of the Magic Alphabet Box Educational Game Tool which has the characteristics of being simple, interesting, fun, durable and long-lasting, easy to use and can improve aspects of student development. (3) The effectiveness of the Box Magic Alphabet educational game tool in introducing letters to early childhood as an effective learning medium. This is because the existence of educational game tools can make it easier for teachers to convey information through the media provided, with a percentage value reaching 92% and is considered very valid. (4) The practicality of the Magic Alphabet Box Educational Game Tool in introducing letters to young children can be seen from its simple use, it does not confuse children and is also easy for teachers to practice, with a percentage score of 96% and is considered very valid.